Glutamate uptake disguises neurotoxic potency of glutamate agonists in cerebral cortex in dissociated cell culture - Rosenberg, PA (J Neurosci, 1992)
The pharmacological properties of glutamate agonists were compared in astrocyte-rich and astrocyte-poor cultures derived from embryonic rat cerebral cortex. The object of this investigation was to determine the extent to which glutamate uptake might influence the receptor-mediated neurotoxic actions of these compounds. In astrocyte-rich cultures, using 30 min exposures, we observed that the potencies of the poorly transported agonists NMDA (35 microM) and D-glutamate (89 microM) were higher than that of L-glutamate (205 microM). In astrocyte-poor cultures, L-glutamate was much more potent, with an EC50 of 5 +/- 4 microM (3–12 microM), for a 30 min exposure, whereas the potencies of NMDA and D-glutamate were essentially unchanged. L- and D-aspartate were also more effective in astrocyte-poor cultures, again with EC50 values of approximately 6–10 microM, as compared with 130 and 108 microM, respectively, in astrocyte-rich cultures. In other experiments, blocking sodium-dependent glutamate uptake in astrocyte-rich cultures, by using a sodium-free medium, made glutamate as potent an agonist as in astrocyte-poor cultures. Finally, we directly assessed the glutamate uptake system in astrocyte-rich and astrocyte-poor cultures and found that uptake was reduced approximately 25-fold in the astrocyte-poor cultures. These results show that in the presence of abundant astrocytes the neurotoxic potencies of L-glutamate, L-aspartate, and D- aspartate are substantially under-estimated.